AN OVERVIEW OF TRENDS AND TECHNIQUES IN PREDICTIVE ANALYTICS - Sujana Kakumanu, Naga; Sridhar, Dr. P.; Mullapudi, Bhargavi (The journal of contemporary issues in business and government, 2022)
The term "predictive analytics" refers to statistical and analytical methods. This phrase was created using statistics, machine learning, database methods, and optimization techniques. Its roots may be traced all the way back to classical statistics. It creates forecasts using both current and historical data. Predictive analytics algorithms may be used to predict unpredictable behavior and future occurrences. To assign a score, predictive analytics approaches will be employed. A larger number suggests a greater chance of an event occurring, whereas a lower number indicates a lower chance. These frameworks tackle a range of commercial and scientific problems by analyzing historical and transactional data trends. These models assist in identifying the risks and opportunities faced by each customer, employee, or management in a business. As interest in decision-support solutions has grown, predictive analytics models have risen to the top. In this article, we’ll go through the methodology, techniques, and applications of predictive analytics.